Self-leadership as an attribute of service leadership: Its relationship to well-being among university students in Hong Kong - Shek, Daniel T. L.; Zhu, Xiaoqin; Dou, Diya; Tan, Lindan (Frontiers in Psychology, 2023)
In the scientific literature, although conceptual models and empirical evidence have shown that leadership attributes are intimately linked to the well-being of followers, there is a lack of studies focusing on leadership in the service economy. According to the Service Leadership Theory, service leadership is a process that satisfies the needs of self, others, and systems (teams, organizations, communities, and societies) in ethical ways (Shek et al., 2015b) that is characterized by leadership competence, character, and care. With specific reference to self-leadership emphasized in service leadership, higher levels of service leadership attributes should promote personal well-being. However, the relationships between “service leadership attributes” and “well-being” in leaders at the intrapersonal level in leadership education among Chinese university students are rarely examined. In this study, we collected data from 198 students to understand the linkages between “service leadership attributes” and “well-being” in university students taking a course on service leadership. For tracking changes in students, we collected both pretest and posttest data on validated measures of “service leadership attributes” (i.e., “knowledge”, “attitude”, and “behavior”) and “well-being” (i.e., “positive youth development attributes” and “life satisfaction”). Results showed that the posttest scores on all three domains of “service leadership attributes” as well as two dimensions of “well-being” encompassing life satisfaction and positive youth development attributes were higher than the respective pretest scores, suggesting that students experienced a shift in a positive direction after taking the course. Cross-lagged analyses showed that pretest service leadership attitude and behavior predicted posttest positive youth development attributes; pretest service leadership behavior predicted posttest life satisfaction. Pretest life satisfaction also predicted posttest service leadership behavior. Findings suggest that there is an intimate relationship between “service leadership attributes” and “well-being” in the “pre-work” context among university students.